Subgroup analysis in RAISE: a randomized, double-blind phase III study of irinotecan, folinic acid, and 5-fluorouracil (FOLFIRI) plus ramucirumab or placebo in patients with metastatic colorectal carcinoma progression - Obermannová, R; Van Cutsem, E; Yoshino, T; Bodoky, G; Prausová, J; Garcia-Carbonero, R; Ciuleanu, T; Garcia Alfonso, P; Portnoy, D; Cohn, A; Yamazaki, K; Clingan, P; et al. (Annals of oncology, 2016)
BACKGROUND: The RAISE phase III clinical trial demonstrated that ramucirumab + FOLFIRI improved overall survival (OS) [hazard ratio (HR) = 0.844, P = 0.0219] and progression-free survival (PFS) (HR = 0.793, P < 0.0005) compared with placebo + FOLFIRI for second-line metastatic colorectal carcinoma (mCRC) patients previously treated with first-line bevacizumab, oxaliplatin, and a fluoropyrimidine. Since some patient or disease characteristics could be associated with differential efficacy or safety, prespecified subgroup analyses were undertaken. This report focuses on three of the most relevant ones: KRAS status (wild-type versus mutant), age (<65 versus ≥65 years), and time to progression (TTP) on first-line therapy (<6 versus ≥6 months). PATIENTS AND METHODS: OS and PFS were evaluated by the Kaplan-Meier analysis, with HR determined by the Cox proportional hazards model. Treatment-by-subgroup interaction was tested to determine whether treatment effect was consistent between subgroup pairs. RESULTS: Patients with both wild-type and mutant KRAS benefited from ramucirumab + FOLFIRI treatment over placebo + FOLFIRI (interaction P = 0.526); although numerically, wild-type KRAS patients benefited more (wild-type KRAS: median OS = 14.4 versus 11.9 months, HR = 0.82, P = 0.049; mutant KRAS: median OS = 12.7 versus 11.3 months, HR = 0.89, P = 0.263). Patients with both longer and shorter first-line TTP benefited from ramucirumab (interaction P = 0.9434), although TTP <6 months was associated with poorer OS (TTP ≥6 months: median OS = 14.3 versus 12.5 months, HR = 0.86, P = 0.061; TTP <6 months: median OS = 10.4 versus 8.0 months, HR = 0.86, P = 0.276). The subgroups of patients ≥65 versus <65 years also derived a similar ramucirumab survival benefit (interaction P = 0.9521) (≥65 years: median OS = 13.8 versus 11.7 months, HR = 0.85, P = 0.156; <65 years: median OS = 13.1 versus 11.9 months, HR = 0.86, P = 0.098). The safety profile of ramucirumab + FOLFIRI was similar across subgroups. CONCLUSIONS: These analyses revealed similar efficacy and safety among patient subgroups with differing KRAS mutation status, longer or shorter first-line TTP, and age. Ramucirumab is a beneficial addition to second-line FOLFIRI treatment for a wide range of patients with mCRC. TRIAL REGISTRATION: ClinicalTrials.gov, NCT01183780.
Keywords: senioři; metastázy nádorů; dvojitá slepá metoda; phase III clinical trial; Double-Blind Method; kolorektální nádory; Ramucirumab; fluoruracil; Fluorouracil; Kaplan-Meier Estimate; monoklonální protilátky; ramucirumab; kamptothecin; Colorectal Neoplasms; mužské pohlaví; Middle Aged; VEGFR-2; mutace; Camptothecin; Kaplanův-Meierův odhad; Antibodies, Monoclonal; Adult; CRC; Irinotecan; Neoplasm Metastasis; Disease-Free Survival; ženské pohlaví; metastatic colorectal carcinoma; Mutation; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; irinotekan; Leucovorin; leukovorin; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Proto-Oncogene Proteins p21(ras); protokoly protinádorové kombinované chemoterapie; RAISE; dospělí; protoonkogenní proteiny p21(ras); Female; Aged; přežití bez známek nemoci; lidé; Male